Design of a Mobile Mechanical Structure for Agricultural Robots. - Musinguzi Bosco (Kabale University, 2023)
The project of design of mobile mechanical structure for agriculture robots is undertaken to solve the problem of farmers buying different mechanical platforms for different crop spacing. This includes the study of the existing mechanical platforms, analyzing the row spacing for different crops, developed the conceptual design, sizing and analyzing the mechanical structure, sizing and wheel arrangement selection, analyzing steering mechanism, analyzing screw and nut. All the components are produced in solid works, assembled and finite element analysis done using ANSYS. Keywords Link mechanism, wheel arrangement selection, crop spacing, steering mechanism and finite element analysis Vl